2015
DOI: 10.1007/s12094-015-1382-z
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the DCLK1 promoter region in circulating free DNA and its prognostic value in lung cancer patients

Abstract: The evaluation of DCLK1 promoter region methylation may be useful in both early diagnosis and prediction of the course of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Dclk1 promoter methylation was found in less then 10% of healthy individuals while almost 50% of the patients diagnosed with lung cancer had detectable levels of the methylated Dclk1 promoter in their plasma, and the methylation status was a predictor of poor survival in these patients. 54 Houchen and colleagues analyzed both circulating tumor cells and the serum of patients diagnosed with pancreatic cancer for Dclk1 expression. In a representative genetically engineered mouse model of pancreatic cancer, greater than 50% of all circulating tumor cells expressed Dclk1.…”
Section: Dclk1 As a Potential Tumor Markermentioning
confidence: 99%
“…Dclk1 promoter methylation was found in less then 10% of healthy individuals while almost 50% of the patients diagnosed with lung cancer had detectable levels of the methylated Dclk1 promoter in their plasma, and the methylation status was a predictor of poor survival in these patients. 54 Houchen and colleagues analyzed both circulating tumor cells and the serum of patients diagnosed with pancreatic cancer for Dclk1 expression. In a representative genetically engineered mouse model of pancreatic cancer, greater than 50% of all circulating tumor cells expressed Dclk1.…”
Section: Dclk1 As a Potential Tumor Markermentioning
confidence: 99%
“…Also, a study by Wang et al found that increased APC and RASSF1A methylation levels in plasma cfDNA 24 hours post chemotherapy were correlated with a positive response to treatment in patients with advanced lung cancer [39]. In addition, in a study conducted to determine the methylation status of the DCLK1 promoter in plasma cfDNA from lung cancer patients across stages, 49.2% of plasma cfDNA samples were methylated [40]. Notably in this study, 73.7% and 39.1% of SCLC and NSCLC samples respectively exhibited DCLK1 plasma cfDNA methylation [40].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…The authors have since patented hypermethylation of hDCLK1 gene promoter as a novel epigenetic biomarker for CRCs in patients. Since then, 5'promoter of hDCLK1 gene has been reported to be hypermethylated in gastric (38), pancreatic (38), and lung cancers (39). Interpretation of data in light of these important discoveries, has however remained ignored by some investigators, who have published since 2014 in this field (36,40).…”
mentioning
confidence: 99%